Ретроспектива, современное состояние и перспективы развития исследований в области создания электроустановок с мощными накопителями электрической и магнитной энергии - Баранов, Михаил Иванович (НТУ "ХПИ", 2007)
Приведены краткие данные из истории изобретения человечеством источников и накопителей электричества, указаны некоторые результаты ретроспективных, современных и перспективных отечественных и зарубежных исследований по созданию и использованию в научных и технологических целях высоковольтных электрофизических установок с мощными накопителями электрической и магнитной энергии.

Brief information from the history of invention of electricity sources and accumulators are presented, some results of domestic and foreign retrospective, current and perspective investigations on creation and utilization, for scientific and technological purposes, of high-voltage electro-physical installations with high-power electric and magnetic energy accumulators given.
Retrospective review, state-of-the-art and perspective development of investigations in the field of creating electric installations with high-power electric and magnetic energy accumulators
Keywords: источники электричества; накопители электричества; высоковольтные электрофизические установки; электрическая энергия; магнитная энергия; history; investigation; high-voltage electrophysical installations; high-power electric accumulators; magnetic energy accumulators